DETERMINAN DURASI MENCARI KERJA DI INDONESIA PADA MASA PANDEMI COVID-19 - Ekowira Susilo (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2022)
The Covid-19 pandemic has caused an economic recession, including a significant increase in unemployment. One of the critical issues of unemployment at the micro level is the duration of the job search. This study aims to analyze the determinants of the duration of job search in Indonesia during the pandemic. The data source used is Sakernas August 2020, with a unit of analysis of the population aged 15-64 years who have been working in the past year and those who are still in search of jobs. The analytical method used is Survival Analysis with Cox Regression. The results showed that those who were not a participant in Kartu Prakerja, had lower education, were older, female, married, household heads, and lived in rural areas tended to have a shorter duration of job search.